2008
DOI: 10.1111/j.1745-7254.2008.00842.x
|View full text |Cite
|
Sign up to set email alerts
|

Slack and Slick KNachannels are required for the depolarizing afterpotential of acutely isolated, medium diameter rat dorsal root ganglion neurons1

Abstract: We conclude that Slack and Slick K(Na) channels are required for DAP of medium diameter rat DRG neurons that regulate DRG action potential repolarization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 21 publications
4
28
0
Order By: Relevance
“…• K Na Channels Are Modulated by NAD ϩ nohistochemical data and is similar to what has been reported earlier (Bischoff et al, 1998;Gao et al, 2008). The K Na channel EC 50 s for Na ϩ was determined to be 53 mM (n ϭ 6) and 55 mM (n ϭ 6) in small neurons (Fig.…”
Section: K Na Channels In Drg Neuronssupporting
confidence: 72%
See 4 more Smart Citations
“…• K Na Channels Are Modulated by NAD ϩ nohistochemical data and is similar to what has been reported earlier (Bischoff et al, 1998;Gao et al, 2008). The K Na channel EC 50 s for Na ϩ was determined to be 53 mM (n ϭ 6) and 55 mM (n ϭ 6) in small neurons (Fig.…”
Section: K Na Channels In Drg Neuronssupporting
confidence: 72%
“…Previous work has documented that K Na channels can be recorded in small-and medium-sized DRG neurons (Bischoff et al, 1998;Gao et al, 2008), and we have now demonstrated that K Na channels are also present in large, proprioceptive DRG neurons. The Na ϩ -doseresponse relationship for K Na channels for both small and large DRG neurons was determined to be similar.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations